An application of the American customer satisfaction index (ACSI) in the South African motor vehicle industry - N. S. Terblanche (South African Journal of Business Management, 2006)
Longer relationships with customers, with an anticipated concomitant increase in profitability flowing from such relationships, have become the focus of many businesses. Over time numerous measures to gauge and predict loyalty and commitment have been developed with the purpose to assist management in this respect. However, one of management's major challenges is to employ a model that is appropriate to explain and predict customer retention for a particular company or brand. This study investigates the reliability of the ACSI for South Africa and reports on the empirical findings in respect of the relationships between various dimensions in the ACSI model as applied in the South African motor vehicle industry. Apart from a paper in press, no research or application of the ACSI has been published in any South African academic journal (Terblanche, 2006). The motor vehicle industry as a whole as well as two individual motor vehicle brands is the focal point of this study. The strengths of various relationships such as, for instance, the relationship between customer satisfaction and customer loyalty and the relationship between customer expectations and perceived value were studied. The interpretations of the findings between the various dimensions, which are useful from both a theoretical and a managerial perspective, are offered.
Keywords: 650